Traffic Management in Telecommunication Networks Using Artificial Intelligence - Zufarova Nargiza Nigmat kizi (Zien Journals, 2022)
Traffic analysis and management tasks form the basis of modern telecommunication management processes. The goal of such solutions is to provide a balance between the volume of traffic, service and telecommunication resources. These tasks, as well as ensuring the effectiveness of technical solutions for a sufficiently long time, are carried out at the stage of designing telecommunications. In this article, a scientific research was conducted on the management of traffic in telecommunication networks using artificial intelligence methods.
Keywords: AI; traffic; telecommunications; resource